An Analysis on Students Problem-Solving Skill and Scientific Literacy Based on Higher Order Thinking Skills (HOTS) Viewed from Gender - Gito Hadiprayitno; Nur Lestari; Kusmiyati Kusmiyati; Akhmad Sukri; Jono Irawan (Postgraduate, University of Mataram, 2022)
Each student has differences in problem-solving, scientific literacy, and higher-order thinking skills. Gender differences partially influence student mindset. The purpose of this study was to analyze the problem-solving skill and scientific literation of students on different genders. The study adopted and modified the one-shot case study design. The subjects of this study were 76 students who took the Animal Ecology course. Both experimental classes were given treatment using practical activities. Data on students' problem-solving skill were collected by using a test consisting of 25 questions. Whereas scientific literacy was collected by using essay questions. Students’ scientific literacy were categorized into 5 scales that were analyzed by using percentages. Statistical analysis uses descriptive and t-tests to determine differences in problem solving skill on different genders. The results showed that (1) 37.66% of students’ scientific literacy are on a multidimensional and conceptual scale, while the remaining 62.34% were on a functional, nominal and literacy scale, (2) students' problem-solving skill are in the medium category, and there is no difference in problem-solving skill in males and females (p>.05).